PENGEMBANGAN MOBILE VILLAGE (M-VILLAGE) MEWUJUDKAN PLERET DESA CERDAS - Sumiyatun; Thomas Edyson Tarigan (LPPM STMIK El Rahma Yogyakarta, 2020)
The potential of the village is the strength, capability and capability of the village which has the possibility to be developed to improve the welfare of the community. Karet Village which is located in Pleret Bantul Village has tourism, handicraft, culinary and cultural potential to be developed towards the Tourism Village. However, it is unfortunate because no application development has been seen so that this potential is not yet known by the wider community. For this reason, efforts are made to make this area more famous so that it can improve the welfare of the local community. This research will develop the concept of a mobile village by building an Android-based mobile technology application to inventory tourism, culinary and cultural potential in Karet Village, Pleret Village, Bantul, as a supporter of the Smart Village concept. This research is expected to be able to provide a mobile application to inventory the potential for tourism, culinary and culture. This application can also be used to support the promotion and realization of the Smart Village concept.